Encryption and Decryption of an Image Data â€“ a Parallel Approach - M E, Raghu; C Ravishankar, K (International Journal of Engineering and Technology, 2018)
Multimedia data has been essential part of our lives, from instant messaging application to social media. Instant messaging applications like WhatsApp uses AES 256 bit key for security purpose. The security measures are taken so as to protect the data from unauthorized access and to ensure privacy. This paper mainly considers image data as source for encryption and decryption. Along with text, AES algorithm is used for image cryptography, in its suitable way. The AES algorithm is chosen because of its highly secured way of encryption and decryption. Time required for the procedure of encryption and decryption is also measured. Present use of Internet, mobile and socialmedia made images considerable value in our daily life.Â  Securing multimedia data is becoming an important issue in communication and storage. Secured communication of digital images is needed in many areas, such as electronic commerce,medical imaging systems, mobile check deposit, online photograph album, military image communication, etc.., There is a need of developing fast encryption methodologies for such communicationÂ